Flow chemistry-enabled studies of rhodium-catalyzed hydroformylation reactions. Issue 62 (10th July 2018) - Zhu, Cheng; Raghuvanshi, Keshav; Coley, Connor W.; Mason, Dawn; Rodgers, Jody; Janka, Mesfin E.; Abolhasani, Milad
Abstract : We present an autonomous microscale flow chemistry platform for high-throughput fundamental and applied studies of homogeneous hydroformylation reactions. Abstract : We present an automated microscale flow chemistry platform for rapid performance evaluation of continuous and discrete reaction parameters in homogeneous hydroformylation reactions. We demonstrate the versatility of the developed microfluidic platform through a systematic study of the effects of a library of phosphine-based ligands on catalytic activity and regioselectivity.